Effect of balance training with Pro-kin System on balance in patients with white matter lesions. Issue 51 (December 2017) - You, Hong; Zhang, Hongxia; Liu, Jia; Han, Tingting; Zhang, Min; Zhao, Weijing; Jiang, Shangrong
Abstract : Abstract: Patients with white matter lesions (WMLs) often present with problems of balance. The aim of this study was to verify the effects of combined Pro-kin system and conventional balance training to improve balance ability in WMLs patients. This is a randomized controlled study, and 40 participants were divided into 2 groups: the intervention group (n=18) received Pro-kin system with additional conventional balance training for 20 minutes per session, 5 times a week, for 2 weeks. The control group (n = 19) received only conventional balance training. Outcome measures were examined before and after the 2 weeks intervention using the Berg Balance Scale (BBS), Timed Up and Go (TUG) test, and Pro-kin system. After completion of the 2 weeks intervention, BBS, TUG, and Pro-kin system results significantly improved in the intervention group ( P < .05). In the control group, BBS and Pro-kin system results significantly improved ( P < .05). Changes in all outcomes but the ellipse area with eye closed ( P < .05) were significantly higher in the intervention group than in the control group. The combination of Pro-kin system and conventional balance training is a potentially valuable treatment for patients with WMLs.